Representasi Hubungan Sipil-Militer Pasca Orde Baru pada Film Autobiography - Muhammad Nuzul Adri; Syamsuddin Azis; Alem Febri Sonni (Jurnal Riset Komunikasi (JURKOM), 2025)
This study analyzes the representation of civil-military relations in the post New Order era as depicted in the film Autobiography. Furthermore, the researcher examines the impact of New Order cultural legacies evident in the film. Autobiography is the first political thriller film after the Reformasi era to reflect the enduring hegemonic influence of military power in contemporary socio-political life. The researcher employs a qualitative-descriptive approach and John Fiske's codes of television concept. The study reveals that the film represents the impact of military dominance across three levels: reality, representation, and ideology. At the reality level, military attributes and the behavior of the character Purna affirm his position as a dominant authority. At the representation level, cinematic techniques such as lighting and dialogue create a tense atmosphere that reflects the military's psychological control over civilians. Finally, at the ideology level, the film's narrative exposes power imbalances and the authoritarian legacies of the past, which continue to influence Indonesia's social and political structures.